The role of the serotonin receptor subtypes 5-HT1A and 5-HT7 and its interaction in emotional learning and memory - Stiedl, Oliver; Pappa, Elpiniki; Konradsson-Geuken, Åsa; Ögren, Sven Ove (Frontiers in Pharmacology, 2015)
Serotonin [5-hydroxytryptamine (5-HT)] is a multifunctional neurotransmitter innervating cortical and limbic areas involved in cognition and emotional regulation. Dysregulation of serotonergic transmission is associated with emotional and cognitive deficits in psychiatric patients and animal models. Drugs targeting the 5-HT system are widely used to treat mood disorders and anxiety-like behaviors. Among the fourteen 5-HT receptor (5-HTR) subtypes, the 5-HT1AR and 5-HT7R are associated with the development of anxiety, depression and cognitive function linked to mechanisms of emotional learning and memory. In rodents fear conditioning and passive avoidance (PA) are associative learning paradigms to study emotional memory. This review assesses the role of 5-HT1AR and 5-HT7R as well as their interplay at the molecular, neurochemical and behavioral level. Activation of postsynaptic 5-HT1ARs impairs emotional memory through attenuation of neuronal activity, whereas presynaptic 5-HT1AR activation reduces 5-HT release and exerts pro-cognitive effects on PA retention. Antagonism of the 5-HT1AR facilitates memory retention possibly via 5-HT7R activation and evidence is provided that 5HT7R can facilitate emotional memory upon reduced 5-HT1AR transmission. These findings highlight the differential role of these 5-HTRs in cognitive/emotional domains of behavior. Moreover, the results indicate that tonic and phasic 5-HT release can exert different and potentially opposing effects on emotional memory, depending on the states of 5-HT1ARs and 5-HT7Rs and their interaction. Consequently, individual differences due to genetic and/or epigenetic mechanisms play an essential role for the responsiveness to drug treatment, e.g., by SSRIs which increase intrasynaptic 5-HT levels thereby activating multiple pre- and postsynaptic 5-HTR subtypes.